1992
DOI: 10.1037/0735-7044.106.5.762
|View full text |Cite
|
Sign up to set email alerts
|

Complementary roles of the orbital prefrontal cortex and the perirhinal-entorhinal cortices in an odor-guided delayed-nonmatching-to-sample task.

Abstract: Continuing efforts toward designing odor-guided tasks for rats that are similar in memory demands to tasks used typically with primates have resulted in the development of a continuous delayed-nonmatching-to-sample (cDNM) task that is guided by olfactory stimuli. The results indicate that normal subjects acquire the cDNM task rapidly and that subsequent performance deteriorates with increases in memory delay or interitem interference. Moreover, different aspects of cDNM performance were shown to be differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
285
6
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(324 citation statements)
references
References 75 publications
32
285
6
1
Order By: Relevance
“…Supporting evidence is based on the findings that lesions of the AI/LO cortex produce deficits in working memory for affect based on taste or odor information (DeCoteau et al, 1997;Di Pietro et al, 2004;Otto & Eichenbaum, 1992;Ragozzino & Kesner, 1999). Further support can be found in a study where sustained neuronal firing was observed in the AI/LO cortex during the delay period in a non-matching-to-sample for odors task (Ramus & Eichenbaum, 2000).…”
Section: Working Memory (Short-term Memory)mentioning
confidence: 89%
See 1 more Smart Citation
“…Supporting evidence is based on the findings that lesions of the AI/LO cortex produce deficits in working memory for affect based on taste or odor information (DeCoteau et al, 1997;Di Pietro et al, 2004;Otto & Eichenbaum, 1992;Ragozzino & Kesner, 1999). Further support can be found in a study where sustained neuronal firing was observed in the AI/LO cortex during the delay period in a non-matching-to-sample for odors task (Ramus & Eichenbaum, 2000).…”
Section: Working Memory (Short-term Memory)mentioning
confidence: 89%
“…Based on the empirical findings that all sensory inputs are processed by the DG subregion of the hippocampus ( (Aggleton, Hunt, & Rawlins, 1986;Jackson-Smith et al, 1993;Kesner et al, 1993;Mumby, Wood, & Pinel, 1992;Otto & Eichenbaum, 1992), it has been suggested that a possible role for the hippocampus might be to provide for sensory markers to demarcate a spatial location, so that the hippocampus can more efficiently mediate spatial information. It is thus possible that one of the main process functions of the hippocampus is to encode and separate spatial events from each other.…”
Section: Pattern Separation --Spatial Attributementioning
confidence: 99%
“…Suzuki, Miller, and Desimone (1997) extended this result to demonstrate that this stimulus-specific firing persisted across multiple intervening stimuli. Buffalo, Reber, and Squire (1998) showed that people with lesions to the perirhinal cortex showed deficits of recognition memory over delays as short as 6 s. Mumby and Pinel (1994) showed that rats with damage to entorhinal and perirhinal cortex were impaired on delayed non-match to sample (DNMS) of trial-unique object at delays as short as 15 s. Otto and Eichenbaum (1992) showed no deficit in a continuous delayed non-match task from fornix transection, but showed a deficit from combined perirhinal/entorhinal lesions at delays of 30 s. This not only points to a role for the parahippocampal regions in memory on the time scale of the recency effect in free recall, but argues against a role of the hippocampus in such processes. Murray and Mishkin (1998), showed that lesions to the amygdala and hippocampus that spared rhinal cortex did not have an effect on DNMS performance, whereas a comparable study showed a severe impairment from rhinal cortex lesions at delays as short as tens of seconds (Meunier, Bachevalier, Mishkin, & Murray, 1993 The first suggestion comes from the finding that hippocampal damage is associated with a disruption of memory for items from the early part of the serial position curve.…”
Section: The Context T a Imentioning
confidence: 99%
“…Given the important role of the entorhinal, perirhinal, and parahippocampal cortices in conveying sensory information to and from the hippocampal formation, it is not surprising that damage to these regions produces a memory impairment in monkeys (Murray and Mishkin, 1986;Zola-Morgan et al, 1989b;Gaffan and Murray, 1992;Suzuki et al, 1993) and rats (Otto and Eichenbaum, 1992). In monkeys, bilateral lesions limited to the perirhinal and parahippocampal cortices (the PRPH lesion) produce a severe anterograde memory impairment that resembles human amnesia.…”
mentioning
confidence: 99%